Analisis Pengaruh Tingkat Pengangguran dan IPM Terhadap Tingkat Kemiskinan di Provinsi Papua - Intan Selfina N. Sinaga; Grace Salindeho (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyze the effect of unemployment rate and Human Development Index (HDI) on poverty rate in Papua Province in 2017-2022. The indicator used to measure unemployment is the Open Unemployment Rate (TPT), the indicator of the Human Development Index (HDI) is the HDI figure and the indicator of poverty rate is the percentage of poor people. The TPT and HDI are independent variables, while the poverty rate is an independent variable. The analysis method uses multiple linear regression analysis which results in a regression equation Yt = 61.944 - 0.525X1 - 0.550X2. From the t-test results, it can be seen that the TPT and HDI variables partially have a negative and significant effect on poverty rate in Papua Province. From the results of the F test, simultaneously, the TPT and HDI affect poverty rate in Papua Province. Those two independent variables are able to explain the movement of poverty rate by 59.5 percent.